Mining and community in South Africa: From small town to iron town Edited by: Lochner Marais, Philippe Burger and Deidre van Rooyen - Cilliers, Juanee (Town and Regional Planning, 2019)
Mining has dominated the development in South Africa for over a century. Although the South African economy is no longer dependent on the mining industry, this book clearly indicates that the mining industry still plays (and will continue to play) an important role in the social and economic fabric of the country.